Compassionate design: considerations that impact the users' dignity, empowerment and sense of security. (2019) - Seshadri, Priya; Joslyn, Cole Hatfield; Hynes, Morgan M.; Reid, Tahira
Abstract : Human-centered design provides a means to help designers create products or systems with 'people' as the focus. Compassionate Design (CD), introduced in this paper, is an approach that addresses niche sensitive needs and involves a way of thinking where designers pay special attention to the users' sense of dignity, empowerment, and security. These niche needs surfaced as a result of analyses of 12 cases situated in sensitive contexts where the users felt vulnerable, had a high level of emotional engagement and were negatively affected by the situation. The designers described their deep concern for the users in various talks and interviews. This paper explains the conception of CD and its development that resulted from iteratively and qualitatively analyzing these cases in which designers were intuitively focusing on niche user needs. Dignity, empowerment and security form the basis of CD and have been contextualized in Maslow's hierarchy of needs after they emerged as a result of the analysis of data. This research sets the platform for a design approach that can help designers to consider the often unarticulated user needs of dignity, empowerment and security, in a more intentional manner and not be left to chance .